PERBEDAAN KEMANDIRIAN ANAK YANG IBUNYA BEKERJA (BERKARIR) DENGAN YANG IBUNYA TIDAK BEKERJA (IBU RUMAH TANGGA) USIA 3-4 TAHUN DI DESA SAWAH KECAMATAN KUANTAN TENGAH KABUPATEN KUANTAN SINGINGI - Mellya Efridha; Zulkifli Zulkifli; Enda Puspitasari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : The Objective this research are : (1) To know independence of child age 3-4 years old whose it mother works (career’s mother) in Sawah Village Kuantan Singingi Districts. (2) To know independence of child age 3-4 years old whose it mother isnot working (housewife) in Sawah Village Kuantan Singingi Districts. (3) To know is there difference of independence child between whose mother works (career’s mother) with mother don’t work (housewife). This research is quantitative’s research, it’s cooperative research that is compare two ore more in one variable. The sample’s research is all of children age 3-4 th years old in Sawah Village Kuantan Singingi District. To get sample use sample jenuh technique, that is use all population to be sample. To get data use observation method. This research use analysis technique t test independence, that is compare 2 variable or more. This research’s result are : (1) Based on indicator table the child whose mother works get factual score’s 433 with percentage 72,16%, in category B (high). (2) The child whose mother don’t work get factual score’s 389 with percentage 64,83%, in category B (high). (3) there isn’t significan difference of independence’s child between children aged 3-4 years old whose working mother (career’s mother) with it not work mother (housewife) in Sawah Village Kuantan Singingi Districts.Keyword: Independence, Mother’s Work Status